(untitled) (Central Medical College Journal, 2023)
Background: Schizophrenia may have a better outcome in low- and middle-income countries. In Bangladesh short-term outcome of drug treatment of schizophrenia is also better. It is required to see the predictors of outcome of drug treatment of schizophrenia in Bangladesh. Objectives: General objective of this study is to assess the outcome of 6-month follow-up of patients with schizophrenia. Specific objective of this study is to find out the predictors of 6-month follow-up outcome of drug treatment in schizophrenia. Methods: Patients with a SCID-1/P diagnosis of schizophrenia (n=42) were assessed prospectively at baseline, at 6-week and at 6-month follow-up. Socio-demographic and relevant variables and questionnaire for family support and previous work record for the study were read in front of the patients and guardians and were filled up by the researcher. Psychopathological measurements were applied at base line by researcher and at 6-week and at 6-month by research assistant for the study population. Results: Follow-up data were available for 38 patients at 6-month and among them 86.85% achieved partial remission, 7.89% had not responded and 5.26% had relapsed. In multivariate analysis by General Linear Model Analysis of socio-demographic and relevant variables with the mean BPRS score as outcome in this study we found that age, education, marital status and history of previous work record were significantly associated with the 6-month treatment outcome. Conclusions: Drug treatment outcome of schizophrenia in Bangladesh is better in short-term follow-up. Increase family support and early management by drugs should be a target for intervention. Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 90-96